Association between body mass index at different levels and risk of gastroesophageal reflux disease: a systematic review with dose-response meta-analysis - Yiqing, Mao; Yangyang, Zhang; Lanshuo, Hu; Wenhao, Zhang; Yixin, An; Yingpan, Zhao; Xudong, Tang (Frontiers in Physiology, 2025)
ObjectiveAlthough obesity is widely reported as an established risk factor for gastroesophageal reflux disease (GERD), divergent findings exist across studies. To address the problems of obsolete data and conflicting findings in previous studies, we conducted a systematic review and meta-analysis to explore the association between body mass index (BMI) and GERD.MethodsWe searched Pubmed, Embase, Cochrane Library, and Web of Science for relevant studies, and obtained the prevalence of symptomatic gastroesophageal reflux (symptomatic GER) or GERD from the original studies for the different BMI groups. International BMI cut-off points were adopted to define underweight, overweight, and obesity. Meta-analysis of this association was performed by calculating the combined relative risk (RR) and 95% confidence intervals (95% CI) using a random-effects model. In addition, subgroup and dose-response analyses were performed to explore subgroup differences and the association between BMI and GERD.ResultsAnalysis of 43 papers (39 cross-sectional studies, 4 case-control studies) with a total of 484,219 study participants showed that BMI was associated with the risk of symptomatic GER (RR = 2.041, 95% CI: 1.507–2.763) and GERD (RR = 1.374, 95% CI: 1.260–1.499). The results of the meta-analysis across different BMI groups suggest that, overweight (BMI ≥25 kg/m2) was an important inflection point for the risk of the diseases. In subgroup analyses comparing obese and non-obese populations, we incorporated other obesity diagnostic indicators and found that these might be a significant source of heterogeneity (p = 0.015). Dose-response analysis showed that for every 10 kg/m2 increase in BMI, the risk of prevalence of gastroesophageal reflux disease increased by 68% (RR = 1.681, 95% CI: 1.326–2.131).ConclusionElevated BMI increases the risk of symptomatic GER and GERD, and BMI is positively and linearly correlated with the risk of GERD. Overweight is an important inflection point for disease risk. High-quality prospective cohort studies are needed to explore the causality between the two factors and underlying mechanisms in the future.